Relationship between spiritual well-being with anxiety and depression among cancer patients - Mohsen Vakili Sadeghi; Mohammad Ali Hossein Tehrani; Hajar Pasha; Angela Hamidia; Majid Nabipour; Soraya Khafri; Mohammad Hadi Yadollahpour (PLoS ONE, 2025)
Background Spiritual health is one of the basic concepts regarding how to deal with the problems caused by the disease. Anxiety and depression are common psychological consequences that affect the treatment process in cancer patients. Therefore, the present study has been conducted to explore relationship between spiritual well-being with anxiety and depression among cancer patients. Methods A total of 200 eligible cancer patients were included in this cross-sectional survey. Questionnaires of the Hospital Anxiety and Depression Scale (HADS) and Spiritual Well-Being Scale (SWB) were provided to patients. Results The mean anxiety and depression scores were 9.98 ± 3.74 and 9.68 ± 3.32, respectively. Nearly half of the patients had anxiety and depression disorders. Age (β = -.300, P = .017) was a significant negative predictor for anxiety, and also education (β = -.885, P = .004) was a significant and negative predictor for depression. The mean score of patients’ spiritual well-being was 76.61 ± 20.01, and its dimensions including existential well-being and religious well-being were 37.35 ± 9.78, and 39.27 ± 10.38, respectively. The majority of patients had a moderate level of spiritual well-being (81%). There was a statistically significant relationship between educational levels and spiritual well-being (P = 049), and religious well-being (P = 033). The spiritual well-being could significantly and negatively predict anxiety (β = -0.154, P < 0.001) and depression (β = -.134, P = < 0.001). There was a significant and inverse relationship between religious well-being with anxiety (rho = -.832, P < 0.001) and depression (rho = -.842, P < 0.001), and between existential well-being with anxiety (rho = -.830, P < 0.001) and depression (rho = -0.813, P < 0.001). There was a significant positive relationship between anxiety and depression (rho = 0.717, P < 0.001). The highest percentage of patients with depression disorder had more anxiety (75.6%). Conclusions Spirituality can serve as a protective factor for psychological morbidity. Spirituality wellbeing-based care programs are suggested as a good method to promote mental health in cancerous patients.